Rekayasa Mesin Pencacah Rumput sebagai Solusi Teknologi Tepat Guna untuk Efisiensi Pakan Ternak Kambing - Sutrisno, Joko; Ginting, Berta Br; Parulian, Sopar; Adam, Hikamah Adwin; Anisa, Septri (Politeknik Negeri Medan, 2025)
One of the main challenges faced by small-scale ruminant farmers is the high cost of feed and the low efficiency of forage utilization, both of which directly increase production costs and reduce profit margins. This community service program aimed to improve goat feed efficiency through the application of appropriate technology in the form of a grass chopping machine, combined with feed management strengthening. The program was implemented with a partner goat farmer in Sumber Karya Village, Binjai Timur District, using a participatory approach that included a needs assessment, the design and fabrication of a 100 kg/hour grass-chopping machine, operational and maintenance training, and feed management assistance. The results indicate that the application of the chopping machine reduced forage waste from approximately 40% to less than 10%, resulting in monthly feed cost savings of up to ±30%. Improved feed efficiency also contributed to faster weight gain and a shorter fattening period. These findings demonstrate that integrating appropriate technology with management support effectively enhances feed efficiency and improves the economic sustainability of smallholder goat farming.